REVIEW PAPER/EDITORIALTumor Necrosis Factor alpha receptors p55 and p75 and ovarian cancer – state-of-the-art research and clinical implications - Rzymski, Paweł (Archives of Medical Science, 2005)
Tumor Necrosis Factor a acts via its two cell-surface receptors p55 and p75 and the effect depends on their activation. Receptors are proteins that dissociate from cell surface and become soluble molecules in serum blocking the natural activity of TNFα. It has been proved that this cytokine and both receptors could be overexpressed and constitutively produced by many malignant tumors, including ovarian cancer. However, little is known about the ovarian-specific role in cancer biology. Molecular and immunological research was not followed by many clinical evaluations of potential power of TNFα, p55 and p75. Some research supports previous laboratory results. It has been also suggested that especially receptors p55 and p75 could be useful in ovarian cancer detection, differentiation, staging or predicting prognosis, relapse and surgical debulking. Results are inspiring and promising, but should be followed by more well-designed research.